Beneficial and toxicological aspects of zinc oxide nanoparticles in animals - Heshu Sulaiman Rahman; Hemn Hassan Othman; Rasedee Abdullah; Hareth Yahya Ahmed Shujaa Edin; Nagi A. AL‐Haj (Veterinary Medicine and Science, 2022)
Abstract Nanotechnology is a far‐reaching technology with tremendous applications in various aspects, including general medicine, veterinary medicine, agriculture, aquaculture, and food production. Nanomaterials have exceptional physicochemical characteristics, including increased intestinal absorption, biodistribution, bioavailability, and improved antimicrobial and catalytic properties. Although nanotechnology is gaining ground in animal management, husbandry, and production, its wide use is still hampered by occasional toxicity and side effects. Zinc oxide nanoparticles (ZnO‐NPs) have long been utilized in animal production, aquaculture, and pet animal medicine. However, the use ZnO‐NPs in animals has been associated with reports of toxicity and side effects. ZnO‐NPs may have shown numerous beneficial effects in animals; its use must be regulated with care to avoid unwanted consequences. Thus, this review emphasizes the usage of ZnO‐NPs in animal production and laboratory animals and the potential side effects associated with the use of nanoparticles as a feed supplement and therapeutic compound.